Changes in serum uteroglobin level in type 2 diabetes mellitus patients - Lim, Joung Youl; Ju, Sang-Hyeon; Kim, Ji Min; Yi, Hyon-Seung; Lee, Ju Hee; Kim, Hyun Jin; Ku, Bon Jeong; Joung, Kyong Hye (Frontiers in Endocrinology, 2024)
Uteroglobin is a multifunctional protein with anti-inflammatory properties. Studies have revealed the importance of inflammation in type 2 diabetes mellitus (T2D) pathogenesis. Here, we investigated the relationship between uteroglobin and T2D.We performed diagnostic tests for diabetes in subjects who had not been diagnosed with or treated for T2D. We established three groups, containing those with normal glucose tolerance (NGT), prediabetes and T2D, consisting of 80 people each, and compared their uteroglobin levels. In addition, 28 patients newly diagnosed with T2D were treated with metformin for 12 weeks, and 63 patients newly diagnosed with dyslipidaemia during the treatment for T2D were treated with statin for 12 weeks.This study showed that uteroglobin levels were significantly lower in prediabetes and T2D groups than in the NGT group. Uteroglobin levels were not significantly correlated with other metabolic parameters, except BMI, HOMA-β and eGFR. In the group treated with metformin or statin, uteroglobin levels increased after treatment compared to before treatment.Uteroglobin is a sensitive factor that was decreased even in prediabetes and increased upon treatment with drugs with anti-inflammatory effects. Uteroglobin is a potential early biomarker that reflects a chronic inflammatory condition in T2D.